Common Bile Duct Stricture Post Open Cholecystectomy - Taufiq Taufiq; Ari Fahrial Syam (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2013)
Common bile duct stricture is a common complication following open cholecystectomy. Approximately 80% of benign strictures occur following injury during a cholecystectomy. We report a female aged 70 years old, with a history of open cholecystectomy due to gallbladder stones. She was admitted to Cipto Mangunkusumo Hospital with symptoms and signs of obstructive jaundice. Endoscopy retrograde cholangio-pancreaticography (ERCP) examination revealed proximal common bile duct (CBD) stricture. She underwent open laparotomy, during which, a narrowing of proximal CBD was seen due to a fibrosis involving part of the duodenum. The patient then underwent a hepatic-duodenostomy bypass surgery. The symptoms and signs of obstructive jaundice were relieved after surgery.Keywords: CBD stricture, obstructive jaundice, open cholecystectomy, ERCP, hepatoduodenostomy bypass surgery